Analisis Manajemen Sumber Daya Manusia pada Perpustakaan Universitas Kapuas Sintang - Tijan, Florensius (Siber Nusantara Publisher, 2023)
Abstract: Library human resources are an important element in the process of library development. In this technological era, library human resources, especially in higher education institutions, are required to be able to maximize skills according to their field of work regarding libraries. This research relies on developing soft skills that need to be carried out by a librarian. so that library services will be maximized for students and lecturers. The results of this study are maximizing the role of Libraries in library development to the fullest by increasing the quality of service which is supported by many factors such as facilities and infrastructure supporters, namely human resources and IT-based library information systems. Abstrak: Sumber daya manusia perpustakaan merupakan elemen penting dalam proses berkembangnya perpustakaan. Pada zaman yang serba teknologi seperti sekarang ini, sumberdaya manusia perpustakaan terutama di Lembaga perguruan tinggi di tuntut untuk bisa memaksimalkan skil sesuai bidang pekerjaan nya tentang perpustakaan. Penelitian ini bertumpu pada pengembangan softskil yang perlu dilakukan oleh seorang pustakawan.sehinga pelayanan perpustakaan akan maksimal kepada mahasiswa dan dosen.Hasil dari penelitian ini adalah memaksimalkan peran Pustaka dalam pengembangan perpustkaan secara maksimal dengan meningkatkan kualitas pelayanan yang di dukung oleh banyak factor seperti sarana dan prasara pendukung yaitu sumber daya manusia serta system informasi perpustakaan berbasis IT.